Copolymer and laminate containing same

By using specific olefin-aromatic vinyl compound-aromatic polyene copolymer and liquid crystal polymer, a laminate of resin layer and metal foil is formed, and the difficulty of low dielectric properties and high adhesion in the prior art is solved. The problem of taking into account both high mechanical properties and excellent low dielectric properties are achieved.

CN119161537APending Publication Date: 2024-12-20DENKA CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411309385.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-05-20
Filing Date
2020-12-01
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The prior art is difficult to achieve cured substances with low dielectric properties and high adhesiveness and metal foils simultaneously, and there are problems of poor processability and fillability.

Method used

Using olefin-aromatic vinyl compound-aromatic polyene copolymers that meet specific conditions, combined with a liquid crystal polymer layer and an appropriate amount of curing agent, elastomer and surface modifier, a laminate of resin layer and metal foil is formed, and the The curing is carried out by hot pressing and photopolymerization.

Benefits of technology

A laminated body with high mechanical properties and excellent low dielectric properties at room temperature or high temperature is realized, and the adhesion to metal foil and the overall performance of cured substances are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005050205770000141
    Figure BDA0005050205770000141
  • Figure BDA0005050205770000142
    Figure BDA0005050205770000142
  • Figure BDA0005050205770000331
    Figure BDA0005050205770000331
Patent Text Reader

Abstract

The invention relates to a copolymer and a laminate containing the same. Provided are: a composition with which it is possible to obtain a cured product having excellent low dielectric properties and high adhesion to a metal foil; and a laminate containing the composition. The laminate contains a resin layer and a metal foil, and the resin layer contains an olefin-aromatic vinyl compound-aromatic polyene copolymer satisfying conditions (1)-(4).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of Chinese invention patent application No. 202080082954.5 (PCT application number is PCT / JP2020 / 044699), whose application date is December 1, 2020 and whose invention name is “Copolymer and laminate containing the same”. Technical Field

[0002] The present invention relates to a copolymer and to a laminate comprising a resin layer containing the copolymer and a metal foil. Background Art

[0003] As communication frequencies develop towards high frequency bands above the gigahertz band, the need for insulating materials with low dielectric properties has also increased. Polyolefins such as polyethylene, aromatic vinyl compound polymers such as polystyrene, etc., do not have polar groups in their molecular structures, and are therefore known as materials that exhibit excellent low dielectric constants and low loss tangents. However, the heat resistance of these polymers depends on the crystal melting point or glass transition temperature, so there is a problem with the heat resistance when used as an electrical insulator, and since they are thermoplastic resins, there is a problem in the film-making process (Patent Document 1).

[0004] Although fluorine resins such as perfluoroethylene have excellent low dielectric constant, low dielectric loss and excellent heat resistance, they are difficult to form and film, and have low device suitability. In addition, there is also a problem of the bonding force between wiring and copper foil. On the other hand, substrates and insulating materials using post-curing resins such as epoxy resins, unsaturated polyester resins, polyimide resins, and phenolic resins are widely used because of their heat resistance and easy handling, but dielectric constants and dielectric loss are relatively high, and as insulating materials for high frequency use, it is expected to be improved (patent document 2).

[0005] An electrical insulating material (patent document 3) formed by a grafted product or a block copolymer formed by a polymer fragment based on an olefin system and a styrene system has been proposed. This material focuses on the low dielectric constant and low dielectric loss of the hydrocarbon polymer of olefin and styrene systems. In this manufacturing method, commercially available polyethylene and polypropylene are subjected to conventional graft polymerization in the presence of styrene monomer, divinylbenzene monomer and a free radical polymerization initiator. This method has the problem that the grafting efficiency cannot be improved and the uniformity of the polymer is insufficient. Furthermore, the obtained polymer contains gel, and there is a problem of poor processability and filling. This material is a thermoplastic resin, and heat resistance is insufficient, and a heat-resistant resin such as 4-methyl-1-pentene system needs to be added. This material is difficult to be applied to a molding method that solidifies it after being coated or filled in a specified position.

[0006] Patent Document 4 describes an insulating layer formed of a crosslinked structure containing a hydrocarbon compound having a plurality of aromatic vinyl groups as a crosslinking component. The cured product of the crosslinking component described specifically in the examples is rigid and it is considered difficult to fill it with a large amount of filler.

[0007] Patent document 5 discloses a cured product obtained by a specific polymerization catalyst, and the cured product is formed by a specific composition and ratio of ethylene-olefin (aromatic vinyl compound)-polyene copolymer and a non-polar vinyl compound copolymer. The cured product specifically recorded in the embodiment of patent document 5 has the characteristics of low dielectric constant and low loss tangent, but because it is soft, it is necessary to improve the mechanical strength such as elastic modulus at room temperature and high temperature. For the insulating material of the film, such as the interlayer insulating material and protective layer use of FPC and FCCL, it is preferred to improve the dimensional stability such as thickness in the installation process or after installation. In addition, the cured product of the composition specifically recorded in the embodiment still has room for improvement in terms of the adhesion with metal foil, particularly copper foil. Patent document 6 discloses a cured product obtained by the same specific polymerization catalyst, and the cured product is formed by a specific composition and ratio of ethylene-olefin (aromatic vinyl compound)-polyene copolymer and a non-polar vinyl compound copolymer, but the cured product of the composition specifically recorded in the embodiment still has room for improvement in terms of the adhesion with metal foil, particularly copper foil, and low temperature characteristics. Patent Document 7 also describes a cured product of a composition containing the same copolymer, but the cured product of the composition specifically described in the examples still has room for improvement in terms of adhesion to metal foil, particularly copper foil.

[0008] In addition, the curable compositions disclosed in Patent Documents 5, 6, and 7 contain a relatively large amount of monomer components (aromatic vinyl compounds, aromatic polyenes) and are in the form of varnishes. Therefore, there is a problem that not only they have a peculiar smell, but also B-stage sheets (semi-cured sheets) cannot be easily produced. These curable compositions have the problem of complex manufacturing equipment.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application Laid-Open No. 52-31272

[0012] Patent Document 2: Japanese Patent Application Laid-Open No. 6-192392

[0013] Patent Document 3: Japanese Patent Application Laid-Open No. 11-60645

[0014] Patent Document 4: Japanese Patent Application Publication No. 2004-087639

[0015] Patent Document 5: Japanese Patent Application Publication No. 2010-280771

[0016] Patent Document 6: Japanese Patent Application Publication No. 2009-161743

[0017] Patent Document 7: Japanese Patent Application Publication No. 2010-280860 Summary of the invention

[0018] Problems to be solved by the invention

[0019] The above-mentioned conventional techniques have not been able to provide a material that can produce a cured product having excellent low dielectric properties and mechanical properties and high adhesion to metal foil, and it is desired to provide such a material.

[0020] Means for solving problems

[0021] That is, the present invention can provide the following aspects.

[0022] A laminate comprising a resin layer and a metal foil, wherein the resin layer comprises an olefin-aromatic vinyl compound-aromatic polyene copolymer satisfying the following conditions (1) to (4).

[0023] (1) The number average molecular weight of the copolymer is 5,000 or more, preferably 20,000 or more and 100,000 or less.

[0024] (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 10% by mass or more and less than 60% by mass.

[0025] (3) The aromatic polyene is one or more polyenes having a carbon number of 5 to 20 and having a plurality of vinyl and / or vinylidene groups in the molecule, and the content of vinyl and / or vinylidene groups derived from the aromatic polyene units is 1.5 to 20 based on the number average molecular weight.

[0026] (4) The olefin is one or more olefins having a carbon number of 2 or more and 20 or less, the olefin is ethylene alone, or the mass ratio of the α-olefin monomer component other than ethylene contained in the olefin to the ethylene monomer component is 1 / 7 or less, and the total of the olefin monomer unit, the aromatic vinyl compound monomer unit and the aromatic polyene monomer unit is 100 mass %.

[0027] An olefin-aromatic vinyl compound-aromatic polyene copolymer that satisfies the following conditions (1) to (4).

[0028] (1) The number average molecular weight of the copolymer is 5,000 or more, preferably 20,000 or more and 100,000 or less.

[0029] (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 10% by mass or more and less than 60% by mass.

[0030] (3) The aromatic polyene is one or more polyenes having a carbon number of 5 to 20 and having a plurality of vinyl and / or vinylidene groups in the molecule, and the content of vinyl and / or vinylidene groups derived from the aromatic polyene units is 1.5 to 20 based on the number average molecular weight.

[0031] (4) The olefin is one or more olefins having a carbon number of 2 or more and 20 or less, the olefin is ethylene alone, or the mass ratio of the α-olefin monomer component other than ethylene contained in the olefin to the ethylene monomer component is 1 / 7 or less, and the total of the olefin monomer unit, the aromatic vinyl compound monomer unit and the aromatic polyene monomer unit is 100 mass %.

[0032] This application relates to the following items:

[0033] Item 1. A laminate comprising a resin layer and a metal foil, wherein the resin layer comprises an olefin-aromatic vinyl compound-aromatic polyene copolymer satisfying the following conditions (1) to (4),

[0034] (1) The number average molecular weight of the copolymer is 5000 or more and 100,000 or less;

[0035] (2) the aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 10% by mass or more and less than 60% by mass;

[0036] (3) the aromatic polyene is one or more selected from polyenes having a plurality of vinyl and / or vinylidene groups in the molecule and having a carbon number of 5 to 20, and the content of vinyl and / or vinylidene groups derived from the aromatic polyene units is 1.5 to less than 20 in terms of number average molecular weight;

[0037] (4) The olefin is one or more olefins having a carbon number of 2 or more and 20 or less, the olefin is ethylene alone, or the mass ratio of the α-olefin monomer component other than ethylene contained in the olefin to the ethylene monomer component is 1 / 7 or less, and the total of the olefin monomer unit, the aromatic vinyl compound monomer unit and the aromatic polyene monomer unit is 100 mass %.

[0038] Item 2. The laminate according to Item 1, wherein the metal foil is copper foil.

[0039] Item 3. The laminate according to Item 1 or 2, further comprising an LCP (liquid crystal polymer) layer.

[0040] Item 4. The laminate according to any one of Items 1 to 3, wherein the resin layer further contains 0.001 to 5 parts by mass of a curing agent based on 100 parts by mass of the copolymer.

[0041] Item 5. A laminate according to any one of Items 1 to 4, wherein the resin layer further contains a total of 1 to 500 parts by mass of one or more additional resins selected from the group consisting of hydrocarbon elastomers, polyphenylene ether resins and aromatic polyene resins, relative to 100 parts by mass of the copolymer.

[0042] Item 6. The laminate according to any one of Items 1 to 5, wherein the resin layer further contains 1 to 500 parts by mass of one or more monomers selected from the group consisting of aromatic vinyl compound monomers, aromatic polyene monomers, and polar monomers, relative to 100 parts by mass of the copolymer.

[0043] Item 7. The laminate according to Item 6, wherein the monomer contains 1 part by mass or more of an aromatic polyene monomer in 100 parts by mass of the monomer.

[0044] Item 8. The laminate according to any one of Items 1 to 7, wherein the copolymer has a vinyl content of 3 or more and less than 20 units in terms of number average molecular weight.

[0045] Item 9. The laminate according to any one of Items 1 to 8, wherein the resin layer further contains one or more selected from the group consisting of a filler, a flame retardant, and a surface modifier.

[0046] Item 10. A cured product obtained by curing the laminate according to any one of Items 1 to 9.

[0047] Item 11. Olefin-aromatic vinyl compound-aromatic polyene copolymer, which satisfies the following conditions (1) to (4):

[0048] (1) The number average molecular weight of the copolymer is 5000 or more and 100,000 or less;

[0049] (2) the aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 10% by mass or more and less than 60% by mass;

[0050] (3) the aromatic polyene is one or more selected from polyenes having a plurality of vinyl and / or vinylidene groups in the molecule and having a carbon number of 5 to 20, and the content of vinyl and / or vinylidene groups derived from the aromatic polyene unit is 1.5 to 20 in terms of number average molecular weight;

[0051] (4) The olefin is one or more olefins having a carbon number of 2 or more and 20 or less, the olefin is ethylene alone, or the mass ratio of the α-olefin monomer component other than ethylene contained in the olefin to the ethylene monomer component is 1 / 7 or less, and the total of the olefin monomer unit, the aromatic vinyl compound monomer unit and the aromatic polyene monomer unit is 100 mass %.

[0052] Item 12. A composition comprising 0.001 to 5 parts by mass of a curing agent based on 100 parts by mass of the copolymer described in Item 11.

[0053] Item 13. A composition comprising 1 to 500 parts by mass of one or more additional resins selected from hydrocarbon elastomers, polyphenylene ether resins and aromatic polyene resins, based on 100 parts by mass of the copolymer described in Item 11.

[0054] Item 14. A composition comprising 1 to 500 parts by mass of one or more monomers selected from the group consisting of aromatic vinyl compound monomers, aromatic polyene monomers, and polar monomers, based on 100 parts by mass of the copolymer according to Item 11.

[0055] Item 15. The composition according to Item 14, wherein the monomer contains 1 part by mass or more of an aromatic polyene monomer based on 100 parts by mass of the monomer.

[0056] Item 16. The composition according to any one of Items 12 to 15, comprising one or more selected from the group consisting of a filler, a flame retardant, and a surface modifier.

[0057] Item 17. A cured product obtained by curing the copolymer according to Item 11 or the composition according to any one of Items 12 to 16.

[0058] Effects of the Invention

[0059] The cured product (cured body) of the copolymer of the present invention or a laminate comprising a resin layer containing the copolymer and a metal foil has high adhesion to the metal foil, excellent low dielectric properties, and can exhibit high mechanical properties at room temperature or high temperature. DETAILED DESCRIPTION

[0060] Hereinafter, further detailed description will be given. The sheet in this specification also includes the concept of film. In addition, even if it is recorded as a film in this specification, it also means the same as the sheet. The "resin layer" in this specification refers to a layer containing the composition of the present invention, and its shape is arbitrary. It is usually in sheet form, and its lateral size and longitudinal thickness relative to the metal foil are arbitrary. In addition, the resin layer may contain materials contained in known insulating layers such as fillers and flame retardants, or the composition may be impregnated in fibers or non-woven fabrics such as glass and ceramics. In addition, it is not limited to sheet form, and it may be hemispherical like a potting material, or it may be strip-shaped, and its shape is arbitrary. The metal foil in this specification is a concept including the wiring of the metal, and its shape is arbitrary, and it may be foil-shaped, linear, or dot-shaped. The metal foil may use commercially available metal foil, or it may be formed by any process such as vapor deposition or plating. Unless otherwise specified, the numerical range in this specification includes its upper limit and lower limit. Content is sometimes referred to as content in this specification.

[0061] In this specification, a laminate means a structure having at least the above-mentioned resin layer and the above-mentioned metal foil in contact and bonding, and the laminated form is arbitrary. Usually, at least the above-mentioned resin layer and the above-mentioned metal foil are laminated in layers, and the number of layers is arbitrary. The resin layer and the metal foil may be adjacent, or may also contain other intervening layers. Examples of laminates include CCL, FCCL, PC, FPC, etc.

[0062] <Composition>

[0063] In this specification, the composition is sometimes described as a resin composition or a curable composition. The composition of the present invention contains the above-mentioned olefin-aromatic vinyl compound-aromatic polyene copolymer having a certain range of composition and molecular weight, and can also contain one or more selected from "curing agent", "monomer", "additive resin", "solvent", "filler", "flame retardant" and "surface modifier".

[0064] <Olefin-aromatic vinyl compound-aromatic polyene copolymer>

[0065] For example, Japanese Patent Publication No. 2009-161743, Japanese Patent Publication No. 2010-280771, and International Publication No. WO00 / 37517 describe methods for producing common olefin-aromatic vinyl compound-aromatic polyene copolymers that can be used in the present invention. The present olefin-aromatic vinyl compound-aromatic polyene copolymer (hereinafter, sometimes abbreviated as "copolymer") satisfies the following conditions (1) to (4).

[0066] (1) The number average molecular weight of the copolymer is 5,000 or more, preferably 20,000 or more and 100,000 or less.

[0067] (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 10% by mass or more and less than 60% by mass.

[0068] (3) The aromatic polyene is one or more polyenes having a carbon number of 5 to 20 and having a plurality of vinyl and / or vinylidene groups in the molecule, and the content of the vinyl and / or vinylidene groups derived from the aromatic polyene units is 1.5 to 20 in terms of number average molecular weight.

[0069] (4) The olefin is one or more selected from olefins having a carbon number of 2 to 20, the olefin is ethylene alone, or the mass ratio of α-olefin monomer units other than ethylene contained in the olefin to ethylene monomer units is 1 / 7 or less, and the total of olefin monomer units, aromatic vinyl compound monomer units and aromatic polyene monomer units is 100 mass%.

[0070] The number average molecular weight of the copolymer is 5,000 or more, preferably 20,000 or more and 100,000 or less, and more preferably 30,000 or more and 100,000 or less.

[0071] The olefin-aromatic vinyl compound-aromatic polyene copolymer can be obtained by copolymerizing monomers of an olefin, an aromatic vinyl compound, and an aromatic polyene.

[0072] In this copolymer, the preferred olefin monomer unit content is 35 mass % or more, particularly preferably 45 mass % or more. The total of the above-mentioned olefin monomer unit, aromatic vinyl compound monomer unit and aromatic polyene monomer unit is 100 mass %. If the olefin monomer unit content is 35 mass % or more, the toughness (elongation) of the cured product finally obtained is improved, and cracking during the curing process, reduction in the impact resistance of the cured product, and cracking in the thermal cycle test of the cured product will not occur. In this copolymer, the preferred olefin monomer unit content is 90 mass % or less.

[0073] Olefin monomer refers to one or more selected from alpha olefins with a carbon number of 2 or more and 20 or less and cyclic olefins with a carbon number of 5 or more and 20 or less, and is substantially free of oxygen, nitrogen, or halogen and is formed by carbon and hydrogen. As alpha olefins with a carbon number of 2 or more and 20 or less, for example, ethylene, propylene, 1-butene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 4-methyl-1-pentene, and 3,5,5-trimethyl-1-hexene can be illustrated. As cyclic olefins with a carbon number of 5 or more and 20 or less, norbornene and cyclopentene can be illustrated. As olefins, a combination of ethylene and alpha olefins other than ethylene and cyclic olefins, or ethylene alone is preferred. The olefin is ethylene alone, or the mass ratio of the alpha olefin monomer component contained in the olefin to the ethylene monomer component is 1 / 7 or less, more preferably 1 / 10 or less, at which time the fracture strength (breaking point strength) and elongation at break (breaking point elongation) of the obtained cured product can be improved, and the peel strength with copper foil and copper wiring can be improved, so it is preferred. It is more preferred that the content of the alpha olefin monomer units other than ethylene in the copolymer is 6% by mass or less, and most preferably 4% by mass or less, or the olefin is ethylene alone. In this case, the peel strength with the copper foil or copper wiring can be further improved, so it is more preferred. For the combination of ethylene and alpha olefins other than ethylene, the glass transition temperature of the ethylene-alpha olefin-aromatic vinyl compound-aromatic polyene chain of the finally obtained cured product varies depending on the type and content of the alpha olefin content, and can be freely adjusted within the range of about -60°C to -5°C.

[0074] The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 or more and 20 or less carbon atoms, and examples thereof include styrene, p-methylstyrene, p-isobutylstyrene, various vinylnaphthalenes, and various vinylanthracenes.

[0075] As an aromatic polyene monomer, a polyene having a carbon number of 5 to 20 and having multiple vinyl groups and / or vinylidene groups in its molecule, preferably a polyene having a carbon number of 8 to 20. As an aromatic polyene monomer, a polyene having a carbon number of 8 to 20 and having multiple vinyl groups in its molecule is preferred, and further preferred are compounds having an aromatic vinyl structure and being substantially free of oxygen, nitrogen, or halogen, such as various divinylbenzenes in the ortho, meta, or para positions or mixtures thereof, divinylnaphthalene, divinylanthracene, p-2-propylene styrene, and p-3-butylene styrene. In addition, a difunctional aromatic vinyl compound described in Japanese Patent Publication No. 2004-087639 can be used, for example, 1,2-bis(vinylphenyl)ethane (abbreviated as: BVPE) is used. Among them, various divinylbenzenes in the ortho, meta, or para positions or mixtures thereof are preferably used, and a mixture of m-divinylbenzene and p-divinylbenzene is most preferably used. In this specification, these divinylbenzenes are referred to as divinylbenzene series. When divinylbenzene-based aromatic polyenes are used, curing efficiency is high during curing treatment and curing is easy, so this is preferred.

[0076] As each monomer of the above olefin, aromatic vinyl compound, aromatic polyene, polar groups can also be contained, such as olefin containing oxygen atoms, nitrogen atoms, aromatic vinyl compounds containing oxygen atoms or nitrogen atoms, or aromatic polyene containing oxygen atoms or nitrogen atoms, but the gross mass of these monomers containing polar groups is preferably less than 10% by mass of the gross mass of this composition, more preferably less than 3% by mass, most preferably not containing the monomer containing polar groups. By being set to less than 10% by mass, the low dielectric properties (low dielectric constant / low dielectric loss) of the cured product obtained by curing this composition can be improved.

[0077] The number average molecular weight of this copolymer is more than 5000, preferably more than 20,000 and less than 100,000, and particularly preferably more than 30,000 and less than 100,000. If the number average molecular weight is more than 5000, preferably more than 20,000, then it is easy to give good physical properties such as high breaking point strength and high breaking point elongation to the final cured product, and it is easy to give toughness, so it is preferred. Specifically, it is preferred to present a tensile breaking point elongation (tensile breaking elongation) of more than 30%. By setting the number average molecular weight to more than 20,000, the composition is not easy to be sticky in the uncured state, and the effect of improving thermoplasticity can be obtained. If the number average molecular weight exceeds 100,000, the molding processing of the composition before curing sometimes becomes difficult. The content of the aromatic vinyl compound monomer unit contained in this copolymer is more than 10% by mass and less than 60% by mass. When the content of the aromatic vinyl compound monomer unit is more than 60% by mass, the glass transition temperature of the cured product of the final composition is near room temperature, and sometimes the toughness at low temperature can be reduced or sometimes the elongation can be reduced, so it is not preferred. In addition, when the content of the aromatic vinyl compound monomer unit is more than 60 mass %, compared with the situation of being less than 60 mass %, sometimes the peel strength with copper foil can be reduced. The content of the aromatic vinyl compound monomer unit contained in this copolymer is particularly preferably more than 10 mass % and less than 55 mass %. If the content of the aromatic vinyl compound monomer unit is less than 10 mass %, the aromaticity of this copolymer is reduced, and the affinity with flame retardant and filler deteriorates, and sometimes flame retardant oozes out, or sometimes filler cannot be filled. In addition, if the content of the aromatic vinyl compound monomer unit is more than 10 mass %, it is possible to obtain a cured product of a composition with a high peel strength with metal foil (particularly copper foil) and copper wiring.

[0078] In the present copolymer, the content of vinyl and / or vinylidene groups derived from aromatic polyene units (hereinafter, the content will sometimes be referred to as content) is 1.5 or more and less than 20, preferably 3 or more and less than 20, based on the unit number average molecular weight of the copolymer. When it is less than 1.5, the crosslinking efficiency is sometimes low, and it becomes difficult to increase the storage modulus at high temperature. The content of vinyl and / or vinylidene groups is sometimes collectively referred to as the "vinyl content" below. By setting the vinyl content within the above range, mechanical properties such as breaking strength and elongation at break at room temperature can be maintained or improved, while the crosslinking efficiency and crosslinking density can be further improved, and it becomes easy to increase the storage modulus at high temperature, so it is preferred. In particular, the effect is significant when the amount of monomer used is low. The vinyl content of the unit number average molecular weight derived from the aromatic polyene unit (divinylbenzene unit) in the present copolymer can be obtained by a person skilled in the art by dividing the number average molecular weight (Mn) converted to standard polystyrene obtained by the known GPC (gel permeation chromatography) method and the number average molecular weight (Mn) converted to polystyrene by the known GPC (gel permeation chromatography) method. 1The vinyl content and vinylidene content derived from the aromatic polyene unit obtained by H-NMR measurement are compared. 1 Comparing the intensity of each peak area obtained by H-NMR measurement, the vinyl content of the copolymer derived from the aromatic polyene unit is 0.095% by mass. When the standard polystyrene conversion number average molecular weight measured by GPC is 68,000, the molecular weight of the vinyl derived from the aromatic polyene unit in the number average molecular weight is the product of these, i.e., 64.8, which is divided by the formula weight of the vinyl, 27, to be 2.4. That is, the vinyl content of the aromatic polyene unit in the copolymer is 2.4 per unit number average molecular weight. 1 The attribution of the peaks obtained by H-NMR measurement is known in the literature. 1 The method of obtaining the composition of the copolymer by comparing the peak areas obtained by H-NMR measurement is also known. In addition, in this specification, the content of the divinylbenzene unit in the copolymer can be determined based on the peak intensity (based on the peak intensity of the vinyl group derived from the divinylbenzene unit) of 1 That is, the content of the divinylbenzene unit is determined based on the content of the vinyl groups derived from the divinylbenzene unit and assuming that one vinyl group is derived from one divinylbenzene unit in the copolymer.

[0079] Examples of the olefin-aromatic vinyl compound-aromatic polyene copolymer in the present copolymer include ethylene-styrene-divinylbenzene copolymer, ethylene-propylene-styrene-divinylbenzene copolymer, ethylene-1-hexene-styrene-divinylbenzene copolymer, and ethylene-1-octene-styrene-divinylbenzene copolymer.

[0080] <Curing agent>

[0081] As the curing agent used in the composition of the present invention, for example, the curing resin, a known curing agent used in the polymerization or curing of existing aromatic polyenes and aromatic vinyl compounds can be used. Such curing agents include free radical polymerization initiators, cationic polymerization initiators, and anionic polymerization initiators, but free radical polymerization initiators are preferably used. Organic peroxide-based (peroxide) and azo-based polymerization initiators are preferred, and can be freely selected according to the application and conditions. A catalog listing examples of organic peroxides can be found on the homepage of NOF Corporation, for example

[0082] https: / / www.nof.co.jp / business / chemical / product01a.html

[0083] https: / / www.nof.co.jp / business / chemical / product01b.html

[0084] Download from https: / / www.nof.co.jp / business / chemical / product01c.html. In addition, examples of organic peroxides are also described in the catalogs of Wako Pure Chemical Industries, Ltd. and Tokyo Chemical Industry Co., Ltd. The curing agent used in the present invention can be obtained from the above-mentioned companies. In addition, photopolymerization initiators using known light, ultraviolet rays, and radiation can also be used as curing agents. As curing agents using photopolymerization initiators, photoradical polymerization initiators, photocationic polymerization initiators, or photoanionic polymerization initiators can be cited. Such photopolymerization initiators can be obtained, for example, from Tokyo Chemical Industry Co., Ltd. In addition, curing can also be performed by radiation or electron beams themselves. In addition, crosslinking and curing can also be performed by thermal polymerization of the contained raw materials without the presence of a curing agent.

[0085] The amount of the curing agent used is not particularly limited, and is generally preferably 0.01 to 10 parts by mass relative to 100 parts by mass of the composition. When using a curing agent such as an organic peroxide (peroxide) or an azo polymerization initiator, the curing treatment is performed at an appropriate temperature and time in consideration of its half-life. The conditions at this time can be selected according to the curing agent, and are generally preferably in a temperature range of about 50°C to 180°C.

[0086] <Single body>

[0087] Relative to 100 parts by mass of the copolymer, the monomer that can be used in the composition of the present invention is 1 to 500 parts by mass, preferably 1 to 200 parts by mass. When the monomer is 200 parts by mass or less, it is easy to give toughness to the final cured product, so it is preferred. Specifically, the tensile elongation at break of the cured product can reach 30% or more, so it is preferred. In order to make a thermoplastic composition, the less the monomer, the easier it is to handle. Relative to 100 parts by mass of the copolymer, it is preferably 30 parts by mass or less, and particularly preferably 10 parts by mass or less. In addition, it is also possible to substantially contain no monomer. The monomer that can be preferably used in the composition of the present invention is an aromatic vinyl compound monomer, an aromatic polyene monomer and / or a polar monomer, and its molecular weight is preferably less than 1000, and more preferably less than 500. The monomer that can be preferably used in the composition of the present invention can be any monomer as long as it can be cured by various curing agents, preferably a monomer that can be polymerized by a free radical polymerization initiator, and more preferably the above-mentioned aromatic vinyl compound and aromatic polyene. In addition, BVPE (1,2-bis(vinylphenyl)ethane) described in Japanese Patent Gazette No. 2003-212941 can also be preferably used. From the perspective of improving the mechanical strength (elastic modulus) of the cured product at high temperatures, the aromatic polyene monomer is preferably more than 1 part by mass and less than 30 parts by mass relative to 100 parts by mass of the copolymer. In addition, a smaller amount of polar monomers can be used for the purpose of imparting adhesion to other materials required as an insulating material or increasing the crosslinking density. As the above-mentioned polar monomers, various maleimides, bismaleimides, maleic anhydride, glycidyl (meth)acrylate, triallyl isocyanurate (TAIC), tri(meth)acrylate isocyanurate, trimethylolpropane tri(meth)acrylate, etc. can be cited. Maleimides and bismaleimides that can be used in the present invention are described in, for example, International Publication No. WO2016 / 114287 and Japanese Patent Application Laid-Open No. 2008-291227, and can be purchased from, for example, Yamato Chemical Industry Co., Ltd. and Designer molecules Inc. From the perspectives of solubility in organic solvents, high-frequency characteristics, high adhesion to conductors, and prepreg formability, the maleimide group-containing compound is preferably a bismaleimide.

[0088] As the bismaleimides, for example, a compound represented by the following formula (d1) can be used.

[0089] Formula (d1)

[0090] [Chemical formula 1]

[0091]

[0092] In the formula, R2 represents a divalent organic group having an aromatic ring.

[0093] Examples of the compound represented by the formula (d1) include compounds represented by the following formula (d2).

[0094] Formula (d2)

[0095] [Chemical formula 2]

[0096]

[0097] (In the formula, R3 represents a single bond or a methylene group, R4 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and n is an integer of 0 to 4.)

[0098] Examples of the compound represented by formula (d2) include bismaleimide BMI-3000H (meta-phenylene bismaleimide) manufactured by Yamato Chemical Industries, Ltd.

[0099] Bismaleimides can also be used as polyaminobismaleimide compounds. Polyaminobismaleimide compounds can be obtained, for example, by subjecting a compound having two maleimide groups at the end to a Michael addition reaction with an aromatic diamine compound having two primary amino groups in the molecule. In the case of obtaining a high crosslinking efficiency by adding a small amount, it is preferred to use a polar monomer having a multifunctional group of more than two functional groups, and examples thereof include bismaleimides, triallyl isocyanurate (TAIC), and trimethylolpropane tri(meth)acrylate. The amount of polar monomer that can be contained in the composition of the present invention is 0.1 to 10 parts by mass, preferably in the range of 0.1 to 5 parts by mass, relative to 100 parts by mass of the copolymer. By using less than 10 parts by mass, the dielectric constant and loss tangent of the obtained cured product become lower. For example, the dielectric constant is less than 3.0 and the loss tangent is less than 0.005.

[0100] <Adding resin>

[0101] The composition of the present invention preferably contains 1 to 500 parts by mass of one or more resins selected from hydrocarbon elastomers, polyphenylene ethers, and aromatic polyene resins (abbreviated as "additional resins" in this specification) in total, based on 100 parts by mass of the copolymer.

[0102] <Hydrocarbon elastomer>

[0103] The amount of hydrocarbon elastomer used in the composition of the present invention is preferably 1 to 500 parts by mass, more preferably 1 to 200 parts by mass, relative to 100 parts by mass of the copolymer. The number average molecular weight of the hydrocarbon elastomer that can be preferably used in the composition of the present invention is 20,000 or more, preferably 30,000 or more, and is selected from one or more elastomers of ethylene or propylene elastomers, conjugated diene polymers or aromatic vinyl compounds-conjugated diene block copolymers or random copolymers, and their hydrogenates (hydrogenated products). The number average molecular weight of the hydrocarbon elastomer is 1000 or more, more preferably 2000 or more, and most preferably 30,000 or more. The number average molecular weight of the hydrocarbon elastomer is preferably 80,000 or less, more preferably 60,000 or less. As ethylene elastomers, ethylene-octene copolymers, ethylene-1-hexene copolymers and other ethylene-α-olefin copolymers, EPR, EPDM can be cited, and as propylene elastomers, random polypropylene, low stereoregularity polypropylene, propylene-1-butene copolymers and other propylene-α-olefin copolymers can be cited.

[0104] As conjugated diene polymers, polybutadiene and 1,2-polybutadiene can be cited. Block copolymers, random copolymers, and hydrogenated products (hydrogenated products) of aromatic vinyl compounds-conjugated dienes can be exemplified by SBS, SIS, SEBS, SEPS, SEEPS, SEEBS, etc. 1,2-polybutadiene that can be preferably used can be obtained, for example, as a product of JSR Corporation. In addition, it can also be obtained from Nippon Soda Co., Ltd. as liquid polybutadiene: product names B-1000, 2000, 3000. In addition, as a copolymer containing a 1,2-polybutadiene structure that can be preferably used, "Ricon 100" of TOTAL CRAYVALLEY can be exemplified. When one or more resins selected from these hydrocarbon elastomers are in liquid form (viscosity of about 300,000 mPa·s or less) at room temperature (25°C), the amount of the resin used is preferably 1 to 100 parts by mass, more preferably 1 to 30 parts by mass, and particularly preferably 1 to 20 parts by mass relative to 100 parts by mass of the copolymer, from the viewpoint of handleability and molding processability (handleability as a thermoplastic resin) of the composition of the present invention in an uncured state.

[0105] <Polyphenylene ether>

[0106] As polyphenylene ether, commercially available known polyphenylene ether can be used. The number average molecular weight of polyphenylene ether is arbitrary. If the molding processability of the composition is considered, the number average molecular weight is preferably less than 10,000, and most preferably less than 5,000. The number average molecular weight is preferably more than 500, and most preferably more than 1,000. In addition, in the case of adding for the purpose of curing the composition of the present invention, it is preferred to modify the molecular end, and / or preferably have multiple functional groups in one molecule. As functional groups, functional groups such as allyl, vinyl, and epoxy groups can be cited, and vinyl, particularly (meth) acrylic groups, and aromatic vinyl groups belonging to free radical polymerizable functional groups are most preferred. That is, in the composition of the present invention, it is particularly preferred that the two functional polyphenylene ethers at both ends of the molecular chain are modified by free radical polymerizable functional groups. As such polyphenylene ethers, Noryl (registered trademark) SA9000 of SABIC can be cited, and it is particularly preferred to use the two functional polyphenylene ether oligomer (OPE-2St) manufactured by MITSUBISHI GAS CHEMICAL COMPANY. The amount of the polyphenylene ether used in the composition of the present invention is preferably 1 to 200 parts by mass, more preferably 30 to 100 parts by mass, based on 100 parts by mass of the copolymer.

[0107] <Aromatic polyene resin>

[0108] Aromatic polyene resins include divinylbenzene reactive multi-branched copolymers (PDV) manufactured by NIPPON STEEL Chemical & Material Co., Ltd. For example, the document "Synthesis of multifunctional aromatic vinyl copolymers and development of novel IPN-type low dielectric loss materials using the same" (Kawabe Masanao et al., Journal of Japan Institute of Electronics Packaging, p. 125, Vol. 12 No. 2 (2009)) describes such PDV. In addition, as aromatic polyene resins, aromatic polyene polymer resins having the above-mentioned aromatic polyene monomers as main constituent units can also be cited.

[0109] <Solvent>

[0110] A suitable solvent may also be added to the composition of the present invention as required. In addition, the amount used is not particularly limited. The solvent is used to adjust the viscosity and fluidity of the composition. In particular, when the composition of the present invention is in the form of a varnish, a solvent is preferably used. The amount of the varnish used is usually in the range of 50 to 1000 parts by mass relative to 100 parts by mass of the copolymer. As the solvent, cyclohexane, toluene, ethylbenzene, xylene, tetralin, acetone, limonene, mixed alkanes, mixed aromatic solvents, etc. are preferably used.

[0111] In the case of a thermoplastic composition, the solvent is preferably less, preferably less than 1 part by mass relative to 100 parts by mass of the copolymer of the present invention, and from the perspective of molding processability and handling of the thermoplastic resin as a composition before curing, and from the perspective of removal during and after curing, it is more preferred that substantially no solvent is used. Substantially no solvent means preferably 5 parts by mass or less, more preferably 1 part by mass or less, and most preferably 0 parts by mass.

[0112] The composition of the present invention may further contain one or more selected from fillers, flame retardants, and surface modifiers relative to the above-mentioned composition. In order to make the composition of the present invention serve as a matrix for a cured product and to have excellent filling properties for other materials during curing, the composition of the present invention contains one or more selected from the above-mentioned fillers, flame retardants, and surface modifiers, so that even after curing, the cured product is likely to exhibit impact resistance and toughness.

[0113] <Filling agent>

[0114] In addition, known inorganic or organic fillers can also be added as needed. These fillers are added for the purpose of controlling the thermal expansion coefficient, controlling thermal conductivity, and reducing the price, and their usage depends on the purpose. When adding inorganic fillers in particular, known surface modifiers, such as silane coupling agents, etc. are preferably used. When the composition with low dielectric constant and low dielectric loss properties, which is one of the purposes of the present invention, is particularly targeted, as inorganic fillers, boron nitride (BN) or silicon dioxide are preferably used, and fused silica is particularly preferred. From the perspective of low dielectric properties, if a large amount of matching fillers are added, the dielectric constant becomes higher, so relative to the copolymer of 100 mass parts, it is preferred to use a filler less than 500 mass parts, and it is further preferred to use a filler less than 400 mass parts. In addition, in order to improve and improve low dielectric properties (low dielectric constant, low dielectric loss positive connection), hollow fillers and fillers with many shapes of voids can also be added.

[0115] In addition, organic fillers such as high molecular weight or ultra-high molecular weight polyethylene can also be used instead of inorganic fillers. From the perspective of heat resistance, it is preferred that the organic filler itself is self-crosslinked, preferably used in the form of particles or powders. These organic fillers can suppress the rise of dielectric constant and loss tangent. The amount of the organic filler used is preferably 10 to 70 volume % in 100 parts by mass of the composition, and more preferably 30 to 50 volume %. Relative to 100 parts by mass of the copolymer, the amount of the filler used is most preferably more than 1 part by mass and less than 400 parts by mass.

[0116] On the other hand, by mixing and dispersing a high dielectric constant insulator filler having a dielectric constant of preferably 3 to 10,000, more preferably 5 to 10,000 at 1 GHz in the composition of the present invention, it is possible to suppress the increase in loss tangent (dielectric loss), and to prepare an insulating cured product having a high dielectric constant insulating layer having a dielectric constant of preferably 3.1 to 20. By increasing the dielectric constant of the film formed by the insulating cured product, the circuit can be miniaturized, the capacitor can be increased in capacity, and it can contribute to the miniaturization of high-frequency electrical components. The high dielectric constant, low loss tangent insulating layer is suitable for capacitors, inductors for resonant circuits, filters, antennas, and the like. As the high dielectric constant insulator filler used in the present invention, inorganic fillers or metal particles subjected to insulation treatment can be cited. For specific examples, there are known high dielectric constant inorganic fillers such as barium titanate and strontium titanate, and other examples are also specifically described in Japanese Patent Publication No. 2004-087639.

[0117] <Flame retardant>

[0118] The composition of the present invention can be mixed with a known flame retardant. From the perspective of maintaining a low dielectric constant and a low loss tangent, preferred flame retardants are known organic phosphorus-based flame retardants such as phosphate esters or their condensates, known bromine-based flame retardants, and red phosphorus. In particular, from the perspective of flame retardancy and low loss tangent, compounds having a plurality of xylene groups in the molecule are preferred among phosphate esters.

[0119] In addition, as flame retardants, antimony compounds such as antimony trioxide, antimony tetroxide, antimony pentoxide, sodium antimonate, or nitrogen-containing compounds such as melamine, triallyl-1,3,5-triazine-2,3,4-(1H,3H,5H)-trione, and 2,4,6-triallyloxy 1,3,5-triazine can also be used as flame retardant aids. The total amount of these flame retardants and flame retardant aids is usually preferably 1 to 100 parts by mass relative to 100 parts by mass of the composition. In addition, 30 to 200 parts by mass of the above-mentioned polyphenylene ether (PPE)-based resins with low dielectric constants and excellent flame retardancy can also be used relative to 100 parts by mass of the flame retardant.

[0120] <Surface Modifier>

[0121] For the purpose of improving the adhesion with fillers, copper plates, and wiring, the composition of the present invention may also contain various surface modifiers. The amount of the surface modifier used is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the composition of the present invention excluding the surface modifier. As the surface modifier, various silane coupling agents, titanate coupling agents, etc. can be cited. For various silane coupling agents and titanate coupling agents, one or more can be used.

[0122] In the present invention, by changing the copolymer, monomer, added resin and the solvent ratio of the composition within the above range, and further by changing the ratio of flame retardant, filler and surface modifier, the fluidization temperature of the curable resin or composition can be adjusted according to its purpose and molding method. Specifically, the composition of the present invention can adopt the product form of "thermoplastic composition" and "varnish". Here, thermoplasticity in this specification refers to preferably uncured, but also includes the concept of semi-cured state (B stage sheet, etc.) and partially cured state.

[0123] As described above, the composition of the present invention can be obtained by mixing, dissolving or melting one or more selected from the copolymer and the curing agent, and monomers, solvents, added resins, fillers, flame retardants, and surface modifiers as required, and the mixing, dissolving, and melting methods can adopt any known methods.

[0124] <Thermoplastic composition and molded article>

[0125] The composition of the present invention uses a copolymer with a molecular weight in a certain range or more. When containing a smaller amount of monomers below a certain amount, since it mainly contains copolymers, it can present the properties of thermoplastic resins. Therefore, under the condition of not causing crosslinking, it can be formed into a sheet, a tube, a short strip, a particle, etc. in a substantially uncured state by a known molding method as a thermoplastic resin, and then crosslinked (cured). Specifically, the number average molecular weight of the copolymer used in the thermoplastic composition is preferably 20,000 or more and 100,000 or less, and more preferably 30,000 or more and 100,000 or less. In addition, relative to 100 parts by mass of the copolymer, the amount of the monomer that can be used in the thermoplastic composition of the present invention is less than 10 parts by mass. It is further preferred that the aromatic polyene monomers such as divinylbenzene and BVPE are more than 0.3 parts by mass relative to 100 parts by mass of the copolymer. It is most preferred to substantially use aromatic polyene monomers such as divinylbenzene and BVPE as monomers. In addition, it is preferred that the thermoplastic composition or the composition is substantially free of solvent. By satisfying all these conditions, the thermoplastic composition of the present invention can be easily molded into a thermoplastic resin in an uncured state.

[0126] In addition, the thermoplastic composition of the present invention is as follows. When the above-mentioned hydrocarbon elastomer (excluding liquid resin) or polyphenylene ether is contained as an added resin in a certain proportion or more, it can be easily molded into a thermoplastic resin in an uncured state. Specifically, it is preferred that the usage amount of the above-mentioned hydrocarbon elastomer (excluding liquid resin) and / or polyphenylene ether is preferably in the range of 30 to 200 parts by mass relative to 100 parts by mass of the copolymer. At this time, the number average molecular weight of the copolymer used is preferably 5000 to 100,000. For the above thermoplastic composition, it can be pre-molded into various shapes such as sheets by utilizing its thermoplasticity below the action temperature of the curing agent, and combined with semiconductor elements, wiring, or substrates as needed to heat cure and bond them.

[0127] That is, the thermoplastic composition according to a preferred embodiment of the present invention is as follows.

[0128] A molded article or cured article formed from a thermoplastic composition, wherein the thermoplastic composition contains 10 parts by mass or less of a monomer per 100 parts by mass of an olefin-aromatic vinyl compound-aromatic polyene copolymer satisfying the following conditions (1) to (4), and substantially contains no solvent. Hereinafter, the cured article refers to, for example, a cured article of the molded article.

[0129] (1) The number average molecular weight of the copolymer is 20,000 to 100,000.

[0130] (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 10% by mass or more and less than 60% by mass.

[0131] (3) The aromatic polyene is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl and / or vinylidene groups in the molecule, and the vinyl content derived from the aromatic polyene unit is 1.5 to 20 per unit number average molecular weight.

[0132] (4) The olefin is one or more olefins having a carbon number of 2 or more and 20 or less, the olefin is ethylene alone, or the mass ratio of the α-olefin monomer component other than ethylene contained in the olefin to the ethylene monomer component is 1 / 10 or less, more preferably the content of the α-olefin monomer component other than ethylene in the copolymer is 4% by mass or less, and the total of the olefin monomer unit, the above-mentioned aromatic vinyl compound monomer unit and the aromatic polyene monomer unit is 100% by mass.

[0133] In addition, the number average molecular weight of the copolymer may preferably be 30,000 to 100,000. It may also contain one or more selected from "curing agent", "additive resin", "filler", "flame retardant" and "surface modifier". Furthermore, a molded body and a cured product of the molded body may be provided, wherein the molded body is a sheet. The sheet may be uncured (semi-cured) to the extent that the sheet shape can be maintained, or it may be a fully cured sheet. The degree of curing of the composition can be quantitatively measured using the known dynamic viscoelasticity determination method (DMA, Dynamic Mechanical Analysis).

[0134] Furthermore, the thermoplastic composition according to another preferred embodiment of the present invention is as follows.

[0135] A molded article or cured product formed from a thermoplastic composition, the thermoplastic composition comprising 100 parts by mass of an olefin-aromatic vinyl compound-aromatic polyene copolymer satisfying the following conditions (1) to (4), and further comprising 1 to 200 parts by mass of one or more resins selected from hydrocarbon elastomers, polyphenylene ether resins and aromatic polyene resins.

[0136] (1) The number average molecular weight of the copolymer is 20,000 to 100,000.

[0137] (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 10% by mass or more and less than 60% by mass.

[0138] (3) The aromatic polyene is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl and / or vinylidene groups in the molecule, and the vinyl content derived from the aromatic polyene unit is 3 to less than 20 in terms of number average molecular weight.

[0139] (4) The olefin is one or more olefins having a carbon number of 2 or more and 20 or less, the olefin is ethylene alone, or the mass ratio of the alpha olefin monomer component other than ethylene to the ethylene monomer component contained in the olefin is 1 / 10 or less, more preferably the content of the alpha olefin monomer component other than ethylene in the copolymer is 4% by mass or less, and the total of the olefin monomer unit, the aromatic vinyl compound monomer unit and the aromatic polyene monomer unit is 100% by mass. Furthermore, the number average molecular weight of the copolymer is preferably 30,000 or more and 100,000 or less. In addition, it may also contain one or more selected from "curing agent", "monomer", "solvent", "filler", "flame retardant" and "surface modifier".

[0140] In addition, a molded body and a cured product of the molded body, wherein the molded body is a sheet.

[0141] The composition of the present invention can be provided by forming the heated and molten composition into a sheet using a known method at a temperature below the action temperature or decomposition temperature of the curing agent. The sheet can be formed by extrusion molding based on a T-die, can utilize a double-roll mill, or can be extruded and laminated to a substrate film. At this time, the composition, the mass ratio of copolymer / monomer, or the selection and adjustment of solvent, added resin, and flame retardant are carried out in a manner that melts below the action temperature or decomposition temperature of the curing agent and becomes solid near room temperature. The sheet at this time is substantially in an uncured state. Then, through various processing and assembly steps, it is finally processed at a temperature and time above the action temperature or decomposition temperature of the curing agent to fully cure. This method is a conventional technique for crosslinking sealant sheets of ethylene-vinyl acetate resin systems for solar cells (solar power generation devices).

[0142] <Compositions and molded products in a semi-cured state (B-stage sheets, etc.)>

[0143] In addition, the composition of the present invention can also be made into a partially cross-linked state, for example, a molded body such as a sheet or a tube in which part of the curing agent contained therein reacts to be in a semi-cured state (so-called B-stage state). For example, by using a variety of curing agents and / or curing conditions with different curing temperatures, it can be semi-cured, the melt viscosity or fluidity can be adjusted, and the B-stage state can be made. That is, the curable resin and the composition can also be formed into a B-stage sheet that is easy to handle through the first-stage curing (partial curing), and the curing (complete curing) of the second stage can be performed after being stacked and crimped on an electronic device or substrate to form the final shape. At this time, the composition is selected, that is, the mass ratio of the copolymer / monomer is selected, and if necessary, a solvent, a resin, or a flame retardant is added, and it is further adjusted to a sheet (B-stage state) in which the composition containing a curing agent such as a peroxide is partially cured, and the device is molded and assembled, and then heated under pressure to fully cure it. As a method for partially curing the composition, a known method can be used, for example, the following method: using peroxides with different decomposition temperatures, treating for a prescribed time at a temperature at which substantially only one curing agent works to obtain a semi-cured sheet, and finally treating for a sufficient time at a temperature at which all curing agents work to completely cure it.

[0144] <Varnish-like composition and molded article thereof>

[0145] The composition of the present invention can be made into a viscous liquid varnish according to its composition and ratio. For example, it can be made into a varnish by using a sufficient amount of solvent. In particular, when it is made into a varnish for use, it is preferred to add a suitable solvent to the composition of the present invention. The solvent is used to adjust the viscosity and fluidity of the varnish that becomes the composition. As a solvent, if the boiling point at atmospheric pressure is high, that is, the volatility is low, the thickness of the coated film becomes uniform, so a solvent with a boiling point above a certain level is preferred. The preferred boiling point is about 130°C to 300°C at atmospheric pressure. As a solvent suitable for such a varnish, xylene, mesitylene, ethylbenzene, limonene, ethylene glycol methyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether, etc. can be used. In addition, relative to 100 parts by mass of the composition of the present invention, its usage amount is preferably in the range of 10 to 2000 parts by mass.

[0146] The varnish-like composition and the molded article thereof of the present invention contain an olefin-aromatic vinyl compound-aromatic polyene copolymer satisfying the following conditions (1) to (4).

[0147] (1) The number average molecular weight of the copolymer is 5,000 to 100,000.

[0148] (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 10% by mass or more and less than 60% by mass.

[0149] (3) The aromatic polyene is one or more polyenes having a carbon number of 5 to 20 and having a plurality of vinyl and / or vinylidene groups in the molecule, and the vinyl content derived from the aromatic polyene unit is 1.5 or more, preferably 3 or more and less than 20, based on the number average molecular weight.

[0150] (4) The olefin is one or more olefins having a carbon number of 2 or more and 20 or less, the olefin is ethylene alone, or the mass ratio of the α-olefin monomer component other than ethylene contained in the olefin to the ethylene monomer component is 1 / 10 or less, more preferably the content of the α-olefin monomer component other than ethylene in the copolymer is 4% by mass or less, and the total of the olefin monomer unit, the above-mentioned aromatic vinyl compound monomer unit and the aromatic polyene monomer unit is 100% by mass.

[0151] The varnish preferably has a low viscosity for ease of coating and impregnation, and therefore the number average molecular weight of the copolymer is more preferably 5,000 to 70,000.

[0152] In addition, it may contain one or more selected from the above-mentioned "additive resin", "curing agent", "monomer", "solvent", "filler", "flame retardant" and "surface modifier".

[0153] In particular, when used as a varnish using a solvent, the "monomer" used is preferably non-volatile. By making it non-volatile compared to the solvent used, for example, in the solvent removal process after the varnish is applied, the monomer can be prevented from volatilizing together with the solvent. As a suitable monomer for use as a varnish using a solvent, the above-mentioned non-volatile polar monomer is generally preferred. As the polar monomer, various maleimides and bismaleimides can be particularly preferably exemplified.

[0154] The varnish-like composition of the present invention can also be prepared by using a polymerization solution containing the copolymer of the present invention obtained by polymerization. For example, it can also be produced by concentrating the polymerization solution or removing residual monomers, adding a solvent, other resin components, various additives, etc. as required, and adjusting the component concentration, solution viscosity, etc.

[0155] For example, the varnish is applied or impregnated onto a substrate, and the solvent is removed by drying, etc., to form an uncured or semi-cured molded body. Usually, the molded body has a sheet, film, or tape form.

[0156] <Curing>

[0157] For the curing of the thermoplastic composition, molded body, semi-cured (B-stage sheet, etc.) composition, molded body, and varnish-like composition, molded body, the curing can be performed by a known method with reference to the curing conditions (temperature, time, pressure) of the curing agent contained. When the curing agent used is a peroxide, the curing conditions can be determined with reference to the half-life temperature disclosed for each peroxide.

[0158] <Cured product obtained from the composition>

[0159] The dielectric constant of the cured product obtained by the copolymer of the present invention is 3.0 or less and 2.0 or more at 10 GHz, preferably 2.8 or less and 2.0 or more, and particularly preferably 2.5 or less and 2.0 or more. The loss tangent is 0.005 or less and 0.0003 or more, preferably 0.003 or less and 0.0005 or more. These dielectric constants and loss tangents can be obtained by any known method by those skilled in the art, for example, can be obtained by a resonator method (resonant cavity perturbation method or balanced circular plate resonator method).

[0160] Furthermore, the volume resistivity of the obtained cured product is preferably 1×10 15Ω·cm or more. These values ​​are preferred values ​​as electrical insulating materials for high frequencies above 3 GHz, for example. The copolymer used in the composition of the present invention is relatively soft and has a large tensile elongation. Therefore, the cured product obtained from the composition using it has the following characteristics: it exhibits sufficient mechanical properties, is relatively soft, has high impact resistance, and can follow the thermal expansion of the substrate. That is, the tensile modulus of the cured product of the present invention measured at room temperature (23°C) is less than 3GPa, is 5MPa or more, preferably 10MPa or more, and more preferably 20MPa or more. In addition, especially when a large amount of fillers are added, the tensile modulus of elasticity can also take a value of 3GPa or more and 20GPa or less. In addition, the tensile breaking point strength is preferably less than 50MPa, and is 10MPa or more, preferably 15MPa or more, and the tensile breaking point elongation (tensile breaking elongation) is preferably 30% or more, and more preferably 50% or more. In addition, especially when a large amount of fillers are added, the tensile breaking point elongation can also take a value of less than 30%. The cured product of the composition of the present invention has sufficient heat resistance in practical applications. Specifically, if specified from the perspective of practical application, the storage modulus of the cured product of the composition of the present invention at 300°C can be 5×10 5 Pa or more, preferably 1×10 6 Pa or more, most preferably 1.2×10 6 Pa or above. Those skilled in the art can refer to the information recorded in this specification and known materials to determine the ratio of the composition having the above-mentioned physical property parameters and easily prepare a cured product. The cured product obtained from the composition of the present invention can exhibit sufficient heat resistance and mechanical properties at high temperatures in practical applications even when the aromatic polyene as a monomer or a component of a monomer in the composition is suppressed to below a certain proportion. As mentioned above, in order to maintain the molding processability as a thermoplastic resin even in an uncured state, it is important to suppress the aromatic polyene as a monomer or a component of a monomer to below a certain proportion.

[0161] The uncured or semi-cured thermoplastic composition of the present invention can be cured by heat and pressure treatment, etc., even without being subjected to adhesive coating or adhesive treatment, so that it can be bonded to a metal foil for wiring (usually copper foil, but also foil of any metal or alloy that can be used for wiring, such as nickel, aluminum, iron, etc.). Specifically, in the above-mentioned olefin-aromatic vinyl compound-aromatic polyene copolymer, by using a copolymer having an aromatic vinyl compound monomer unit content of 10% by mass or more, and by making the olefin be ethylene alone, or by making the mass ratio of the α-olefin monomer component other than ethylene contained in the olefin to the ethylene monomer component be 1 / 7 or less, it is possible to impart a peel strength of 1.0 N / mm or more when measured in accordance with Japanese Industrial Standard (JIS) C6481:1996. It is further preferred that in the above-mentioned copolymer, the olefin is ethylene alone, or the mass ratio of the alpha olefin monomer component other than ethylene contained in the olefin to the ethylene monomer component is less than 1 / 10, and it is more preferred that the content of the alpha olefin monomer component other than ethylene in the copolymer is less than 4% by mass, so that the peel strength can be further improved, for example, a peel strength of more than 1.3N / mm can be given, so it is more preferred. Generally, it is known that the dielectric properties of laminates such as copper-clad laminates will deteriorate due to adhesive coating or bonding treatment. It is preferred that even if such treatment is not performed, a peel strength of more than 1.0N / mm can be given when measured based on Japanese Industrial Standard (JIS) C6481:1996. In this way, the uncured or semi-cured thermoplastic composition of the present invention can be bonded to the metal foil for wiring by curing treatment such as heating and pressure treatment, without the need for special adhesive coating or bonding treatment. However, in the present invention, imparting adhesion to metal foil and other members does not prevent further implementation of other measures for imparting adhesion (adhesive coating, adhesive treatment, etc.) including the addition of the above-mentioned "surface modifier".

[0162] <Metal Foil>

[0163] The metal foil of the present invention may be any metal foil as long as it can be used for wiring and substrates, for example, copper foil, aluminum foil, nickel foil, etc. The thickness is not particularly limited, and is usually 1 to 500 μm, preferably in the range of 5 to 100 μm. As the metal foil, a copper foil suitable for high frequencies can be used, which may be a rolled copper foil or an electrolytic copper foil. For example, the copper foil may be a copper foil having a surface roughness (maximum height) Rz of preferably 5 μm or less, particularly preferably 3 μm or less as specified in JIS B0601:2001. Such copper foil can be obtained from Furukawa Electric Co., Ltd., JX Metals Co., Ltd., Mitsui Mining & Smelting Co., Ltd., etc.

[0164] <General Use>

[0165] The composition of the present invention can be used as various insulating materials for wiring, preferably for wiring of high-frequency signals, such as protective layers, solder resists, build-up materials, interlayer insulating agents, bonding sheets, interlayer adhesives, and bump sheets for flip chip bonding machines. In addition, it can be used as an adhesive layer for substrates / substrates such as single-layer or multi-layer printed substrates, flexible printed substrates, CCL (copper clad laminates), and FCCL (flexible copper clad laminates) substrates.

[0166] <Laminate containing copolymer or composition and metal foil, and method for producing cured product thereof>

[0167] The preparation method of the laminate containing metal foil and its cured product is not particularly limited, and known methods can be used. For example, it is possible to laminate the thermoplastic composition and metal foil in uncured, B-stage state with known methods, and heat and pressurize them under appropriate conditions to obtain the cured product of the laminate. Alternatively, it is also possible to further laminate and heat them as required by coating or applying the varnish-like composition on the metal foil. The laminate can also be a laminate containing a resin layer containing olefin-aromatic vinyl compound-aromatic polyene copolymer and a metal foil adjacent to the above-mentioned resin layer. When using a solvent in the varnish, it can be cured after removing the solvent under suitable conditions before curing, and it is also possible to heat and remove the solvent after curing, and it is also possible to cure and remove the solvent simultaneously. These can be appropriately adjusted by selecting a solvent or monomer with a suitable vapor pressure and a curing agent with suitable curing conditions.

[0168] <Application of a laminate comprising a copolymer or a composition and a metal foil, and a cured product thereof>

[0169] The metal foil-containing laminate of the present invention and its cured product can be used to manufacture electronic components such as printed substrates, flexible copper-clad laminates with copper foil bonded to resin sheets (films), flexible printed wiring boards with electronic circuits formed on flexible copper-clad laminates, flexible printed wiring boards with reinforcing boards bonded to flexible printed wiring boards and reinforcing boards, multilayer boards formed by stacking and bonding flexible copper-clad laminates and flexible printed wiring boards, and flexible flat cables (also called FFCs) with copper wiring bonded to substrate films. In this specification, metal foil or copper foil is a concept that includes metal wiring or copper wiring.

[0170] <Application of uncured or partially cured sheet of the composition>

[0171] The composition of the present invention can be used as a protective layer, solder resist, laminated material, interlayer insulator, interlayer adhesive, laminated film, bonding sheet, protective layer sheet, bump sheet for flip chip bonding machine, and potting material due to its high bonding strength with metal foil. The uncured sheet or partially cured sheet of the composition of the present invention can be preferably used as an electrical insulating material for high frequency. For example, it can be preferably used as an insulating layer or adhesive layer for a bump sheet or substrate for a laminated film, a bonding sheet, a protective layer sheet, a flip chip bonding machine. By using this composition to replace the epoxy resin and silicone resin used in the past and performing curing treatment, a cured insulating layer and a cured matrix phase with a low dielectric constant and low dielectric loss can be formed. The thickness of the sheet is generally 1 to 300 microns. The sheet can contain woven fabrics and non-woven fabrics such as glass cloth and ceramic fibers, and can also impregnate woven fabrics and non-woven fabrics such as glass cloth or ceramic fibers, and can also form multiple layers with woven fabrics and non-woven fabrics such as glass cloth or ceramic fibers. In addition, as antenna cables for mobile phones, etc., soft and flexible wiring that is partially or completely insulated by using this sheet can be used instead of conventional coaxial cables. By using, for example, LCP (liquid crystal polymer) or PPE sheet, fluorine resin, polyimide resin, etc. as a substrate, covering the wiring with the sheet or B-stage sheet (protective layer sheet) of the present invention and curing it, it can be insulated or bonded to the substrate to be used as an insulating material.

[0172] The laminated body containing metal foil of the solidified product obtained by using the composition of the present invention as an insulating layer can become a wiring substrate with less dielectric loss and excellent high-frequency characteristics. At this time, in addition to low dielectric loss, the heat resistance of the solder, the softness and elongation and impact resistance to a certain extent of the strain caused by the thermal cycle or thermal expansion difference also become advantages. For example, it can be made by laminating and pressing the conductor foil with the insulating layer formed by this solidified product, such as the core material of the general resin plate, general laminated board, etc., such as the cloth, non-woven fabric, film material, ceramic substrate, glass substrate, epoxy resin, etc. formed by glass and quartz. In addition, the slurry or solution containing the curable composition can also be applied to the core material and dried and cured to form an insulating layer. The thickness of the insulating layer is generally 1 to 300 microns. This multilayer wiring substrate can also be multilayered and integrated and used.

[0173] In addition, the composition or copolymer of the present invention can be cured together with the LCP (Liquid Crystal Polymer) layer under relatively mild curing conditions to impart high bonding strength. Specifically, the LCP layer here can be an LCP sheet or an LCP film. Therefore, for example, various laminates of LCP sheets, metal foils (preferably copper foils), and compositions of the present invention can be made. The number of layers and the stacking order of the laminate are arbitrary. As an example of the present invention, the composition of the present invention is useful as an adhesive layer between a metal foil (copper foil) and an LCP sheet. The composition of the present invention can exhibit high adhesion to both metal foils and LCP sheets. In the past, the bonding of LCP sheets and copper foils required heating to the melting point of LCP (approximately 280°C to 330°C, or a temperature close thereto) and crimping. However, by using the composition of the present invention as an adhesive layer, LCP and metal foil can be bonded by crimping at a lower temperature (substantially near the curing temperature of the composition of the present invention). At this time, the low dielectric constant and low loss tangent of the cured product of the composition of the present invention can give the usefulness of the present laminate, especially as a wiring for high-frequency signal transmission. As another example of the present laminate, a structure in which a metal wiring, preferably a copper wiring, arranged on the LCP layer is covered with a cured product layer of the composition of the present invention from the side opposite to the LCP layer side can be cited. It is used as a so-called protective layer on the LCP substrate wiring.

[0174] Here, LCP (liquid crystal polymer) refers to a thermoplastic polymer having a liquid crystal state or optical birefringence when melted. As LCP, there are lyotropic liquid crystal polymers that exhibit liquid crystal properties in a solution state and thermotropic liquid crystal polymers that exhibit liquid crystal properties when melted. Liquid crystal polymers can be divided into type I, type II, and type III according to the thermal deformation temperature, and can be of any type. As liquid crystal polymers, for example, thermoplastic aromatic liquid crystal polyesters, or thermoplastic aromatic liquid crystal polyester amides into which amide bonds are introduced, etc. can be cited. LCP can also be a polymer into which imide bonds, carbonate bonds, carbodiimide bonds, isocyanate bonds, and other bonds derived from isocyanates are further introduced into aromatic polyesters or aromatic polyester amides. As LCP, a molten liquid crystal forming polyester formed by 2-hydroxy-6-naphthoic acid and p-hydroxybenzoic acid can also be used, such as the LCP resin manufactured by Ueno Pharmaceutical Co., Ltd. (model A-5000, melting point 280°C).

[0175] The melting point of LCP is preferably 220-400°C, more preferably 260-380°C, when using the DSC method. If the melting point is within the above range, a film or sheet having excellent extrusion moldability and excellent heat resistance can be obtained. Such LCP can be obtained, for example, from Ueno Pharmaceutical Co., Ltd., Sumitomo Chemical Co., Ltd., and Polyplastics Co., Ltd. Here, the LCP sheet refers to a known LCP sheet, and its thickness is also arbitrary. The LCP sheet can be obtained by known methods such as a T-die extrusion method, a blow molding method, and an endless belt (double belt pressing) method.

[0176] Example

[0177] The present invention will be described below using examples, but the present invention should not be construed as being limited to the following examples.

[0178] The copolymers obtained in the Synthesis Examples and Comparative Synthesis Examples can be analyzed by the following means.

[0179] The content of vinyl units derived from ethylene, hexene, styrene, and divinylbenzene in the copolymer can be determined according to 1 The peak area intensity attributable to each vinyl unit obtained by H-NMR measurement is determined by dissolving the sample in deuterated 1,1,2,2-tetrachloroethane and measuring at 80 to 130°C.

[0180] The molecular weight was determined by using GPC (gel permeation chromatography) to determine the number average molecular weight (Mn) in terms of standard polystyrene. The measurement was performed under the following conditions.

[0181] (When the number average molecular weight is 1000 or more)

[0182] Chromatographic columns: Two TSK-GEL MultiporeHXL-M

[0183] (manufactured by TOSOH CORPORATION) are used in series.

[0184] Column temperature: 40°C

[0185] Solvent: THF

[0186] Liquid delivery flow rate: 1.0ml / min.

[0187] Detector: RI detector (differential refractive index detector)

[0188] When the copolymer is not easily soluble in THF solvent, for example, when the styrene content in the ethylene-styrene-divinylbenzene copolymer is less than 40% by mass, the molecular weight in terms of standard polystyrene is determined by the following high temperature GPC method. The measurement is performed under the following conditions.

[0189] Device: HLC-8121GPC / HT manufactured by TOSOH CORPORATION

[0190] Chromatographic columns: 3 TSKgelGMHHR-H(20)HT,

[0191] Column temperature: 140°C,

[0192] Detector: RI,

[0193] Solvent: o-dichlorobenzene,

[0194] Liquid delivery flow rate: 1.0ml / min,

[0195] Sample concentration: 0.1wt / vol%, injection volume: 100μL

[0196] <DSC measurement>

[0197] DSC measurement was performed using DSC6200 manufactured by Seiko Instruments Inc. under nitrogen flow. That is, 10 mg of resin was used, 10 mg of α-alumina was used as an internal standard, and an aluminum pan was used to heat the sample from room temperature to 240°C at a heating rate of 10°C / min in a nitrogen atmosphere, and then cooled to -120°C at 20°C / min. Then, DSC measurement was performed while heating the sample to 240°C at a heating rate of 10°C / min to determine the glass transition temperature. The glass transition temperature referred to here is the extrapolated glass transition starting temperature of JIS K7121:2012, that is, the temperature of the intersection of the straight line extending from the low temperature side baseline to the high temperature side and the tangent line at the point where the slope of the curve of the step-like change portion of the glass transition becomes the maximum.

[0198] <Tensile test>

[0199] Based on JIS K-6251:2017, a film with a thickness of about 1 mm was cut into a No. 2 dumbbell-shaped 1 / 2 test piece shape, and measured using TENSILON UCT-1T manufactured by ORIENTEC CO., LTD. at 23°C and a tensile speed of 500 mm / min to determine the tensile elastic modulus, tensile breaking point strength (breaking strength), and tensile breaking point elongation (breaking elongation).

[0200] <Measurement of storage modulus>

[0201] The dynamic viscoelasticity measuring device (Rheometric Scientific, Inc., RSA-III) was used to measure the storage modulus at a frequency of 1 Hz and a temperature range of -60°C to +300°C. The storage modulus was determined by cutting a sample (3 mm × 40 mm) from a film with a thickness of about 0.1 mm to 0.3 mm. The main measurement parameters involved in the measurement are shown below.

[0202] Measuring frequency 1Hz

[0203] Heating rate: 3℃ / min

[0204] Sample measurement length 13mm

[0205] Test Type = Dynamic Temperature Ramp (DTempRamp)

[0206] Initial Static Force: 5.0g

[0207] Auto Tension Sensitivity: 1.0g

[0208] Maximum automatic stretching rate 0.033mm / s

[0209] Maximum applied strain: 1.5%

[0210] Minimum allowable torque (Min Allowed Force) 1.0g

[0211] Strain 0.1%

[0212] <Water absorption>

[0213] The measurement was carried out in accordance with ASTM D570-98.

[0214] <Dielectric constant and dielectric loss (loss tangent)>

[0215] The dielectric constant and loss tangent of the cured product of the composition were measured at 23°C and 10 GHz using a cavity perturbation method (8722ES network analyzer manufactured by Agilent Technologies Japan, Ltd., cavity resonator manufactured by Kanto Denshi Applied Development). A 1 mm × 1.5 mm × 80 mm sample was cut from the composition sheet.

[0216] <Olefin-aromatic vinyl compound-aromatic polyene copolymer>

[0217] With reference to the manufacturing method of Japanese Patent Publication No. 2009-161743, Japanese Patent Publication No. 2010-280771, and International Publication No. WO00 / 37517, the monomer type, monomer amount, ratio, polymerization pressure, and polymerization temperature are appropriately changed to obtain copolymers of P-1 to P-7. The total of olefin monomer units (ethylene, 1-hexene), aromatic vinyl compound monomer units (styrene), and aromatic polyene monomer units (divinylbenzene) is set to 100 mass %. The composition, number average molecular weight, and glass transition temperature of the copolymer are shown in Table 1.

[0218] The raw materials are as follows.

[0219] For divinylbenzene, divinylbenzene (meta- and para-mixture, divinylbenzene purity 81%) manufactured by NIPPON STEEL Chemical & Material Co., Ltd. was used. A difunctional polyphenylene ether oligomer (OPE-2St, number average molecular weight 1200, toluene solution) manufactured by MITSUBISHI GAS CHEMICAL COMPANY was further diluted with toluene, and a large amount of methanol was added for methanol precipitation. After air drying, it was dried under reduced pressure to obtain a powdered polyphenylene ether oligomer, and the powdered polyphenylene ether oligomer was used. This powder was used both when kneading with a Brabender plasticizer and when making varnish. SEBS used H-1041 (number average molecular weight 58000) manufactured by Asahi Kasei Chemicals Corporation. The curing agent used was PERCUMYL D (dicumyl peroxide), PERBUTYL O (tert-butyl peroxy-2-ethylhexanoate) or PERHEXYNE 25B (2,5-dimethyl-2,5-bis(tert-butyl peroxide)-3-hexyne) manufactured by NOF Corporation. The 1,2-polybutadiene used was liquid polybutadiene B-3000 (number average molecular weight 3200) manufactured by Nippon Soda Co., Ltd.

[0220] [Table 1]

[0221]

[0222] [Table 2]

[0223]

[0224] Example 1

[0225] Using a Brabender plasticizer (PL2000 manufactured by Brabender), the pre-kneaded resin P-1 (ethylene-styrene-divinylbenzene copolymer) and monomers were added, and kneaded at 100° C. and a rotation speed of 50 times / min for 5 minutes. Further, 1 part by mass of a curing agent (dicumyl peroxide, PERCUMYL D, manufactured by NOF Corporation) was added relative to 100 parts by mass of the total of the resin and the monomer (the total of the raw materials other than the curing agent), and kneaded at 100° C. and a rotation speed of 50 times / min for 5 minutes to prepare a composition. The obtained curable composition was sandwiched between a mold frame and two Teflon (registered trademark) sheets to make them airtight, and pressed by a hot press method (120° C., time 5 minutes, pressure 1.5 MPa) to obtain sheets (uncured sheets) of various thicknesses (thickness 1.0 mm, 0.5 mm, etc.). Each Teflon (registered trademark) sheet is sandwiched between glass plates and a load is applied to make it close, and the obtained sheet is cured by heat treatment at 120°C for 30 minutes, 150°C for 30 minutes, and then 180°C for 120 minutes. After curing, the glass plates, Teflon (registered trademark) sheets and mold frames are removed to obtain a cured sheet of the composition of the present invention.

[0226] Embodiments 2 to 5

[0227] The composition was prepared in the same procedure as in Example 1 with the proportions in Table 2 (the proportions in the table represent parts by mass). In Examples 3 and 4, the raw materials other than the curing agent were kneaded at 120°C and a rotation speed of 30 times / min for 10 minutes, and then the curing agent was added, and kneading was further performed for 5 minutes under the same conditions. PERHEXYNE 25B was used as a curing agent in Example 3. Press molding was performed in the same manner as in Example 1 to obtain an uncured sheet. The properties (room temperature) of the uncured sheets of Examples 1 to 5 were all soft resin-like sheets, which were easy to handle as sheets. Even if they were peeled off from the Teflon (registered trademark) sheet after pressing, the self-adhesiveness of the sheet itself was low and it could be handled as a separate sheet. That is, it is easy to perform molding processing as a thermoplastic resin in an uncured state. In addition, in Examples 3 and 4, the curing was performed by heating at 120°C for 30 minutes, 150°C for 30 minutes, and then 200°C for 120 minutes. In addition, in Example 5, 1,2-polybutadiene was added before adding the curing agent.

[0228] Examples 6 to 7, Comparative Examples 1 to 3

[0229] Add the raw materials other than the curing agent in the proportions shown in Table 2 to a container equipped with a heating and cooling jacket and a stirring paddle, raise the temperature to 60°C and stir to obtain a varnish-like (viscous liquid) composition. Then add the curing agent and stir to dissolve it. PERBUTYL O was used as the curing agent. The obtained varnish-like composition was tightly clamped between a mold frame and two Teflon (registered trademark) sheets to make it airtight, clamped with glass plates and applied with a load to make it fit tightly, and heated in a dryer at 80°C for 12 hours to cure it. After curing, remove the glass plate, Teflon (registered trademark) sheet and mold frame to obtain a cured sheet of the composition.

[0230] In Comparative Examples 1 and 2, the mass ratio of the α-olefin monomer component other than ethylene to the ethylene monomer component contained in the olefin exceeded 1 / 7. In Comparative Example 3, the content of the aromatic vinyl compound monomer unit was 60% by mass or more.

[0231] Examples 8 to 10, Comparative Example 4

[0232] In a container equipped with a heating and cooling jacket and a stirring paddle, raw materials other than the curing agent are added in the ratio shown in Table 2, and the temperature is raised to 60°C and stirred to obtain a varnish-like (viscous liquid) composition. Then, a curing agent is added and stirred to dissolve. As for the curing agent, diisopropylbenzene peroxide is used in Examples 8 and 10, and PERHEXYNE 25B is used in Example 9. In addition, in Examples 8 and 9, 1,2-polybutadiene is added before adding the curing agent. The obtained varnish-like composition is injected into a Teflon (registered trademark) mold frame on a Teflon (registered trademark) sheet, placed in a blower dryer at about 100°C for 6 hours to volatilize the solvent, and then the Teflon (registered trademark) mold frame is carefully removed, and a soft resin-like sheet is obtained. The obtained sheet is clamped between a mold frame and two Teflon (registered trademark) sheets to make them close and sealed, and pressed by hot pressing (120°C, time 5 minutes, pressure 1.5 MPa) to obtain sheets (uncured sheets) of various thicknesses (thickness 1.0 mm, 0.5 mm, etc.). The sheet is easy to handle, and even if it is peeled off from the Teflon (registered trademark) sheet, the sheet itself has low self-adhesiveness and can be handled as a separate sheet. That is, it is easy to perform molding processing as a thermoplastic resin in an uncured state. Each Teflon (registered trademark) sheet is clamped with a glass plate and a load is applied to make it close. In Examples 8 and 9, the obtained sheet is cured by heating at 120°C for 30 minutes, 150°C for 30 minutes, and then 180°C for 120 minutes. In Example 10 and Comparative Example 4, the obtained sheet is cured by heating at 120°C for 30 minutes, 150°C for 30 minutes, and then 200°C for 120 minutes. After curing, the glass plate, Teflon (registered trademark) sheet and mold frame were removed to obtain a cured sheet of the composition of the present invention.

[0233] The cured products of the composition sheets obtained in Examples 1 to 10 can measure the elastic modulus even at 300°C in the viscoelastic spectrum measurement without melting fracture, and the storage modulus at 300°C (573K) is 5×10 5 Pa or above, substantially 1×10 6 Pa or more. In addition, they all show a tensile elastic modulus of less than 3GPa and more than 3MPa. In addition, the tensile breaking point strength is all above 5MPa, and the tensile breaking point elongation is all above 50%. The dielectric constant and loss tangent also meet the scope of the present invention. The water absorption of the cured film obtained in Examples 1 to 10 is all less than 0.1% by mass. On the other hand, the tensile elastic modulus of the cured product of the sheet obtained in Comparative Example 1 is too low at room temperature, and the tensile breaking point strength is also low. The tensile breaking point strength of the sheet obtained in Comparative Example 2 is low.

[0234] <Peel strength from copper foil>

[0235] A copper foil (VSP series, TQ-M7-VSP, thickness 12 μm) manufactured by Mitsui Mining and Smelting Co., Ltd. was used.

[0236] The peel strength measurement with the copper foil was evaluated at 90° peeling in accordance with Japanese Industrial Standard (JIS) C6481:1996.

[0237] <Peel strength from the rough surface of copper foil>

[0238] A copper foil (VSP series, TQ-M7-VSP, thickness 12 μm, surface roughness 1.1 μm) manufactured by Mitsui Mining & Smelting Co., Ltd. was used.

[0239] The uncured sheets (thickness 0.3-0.5 mm) obtained in each embodiment and comparative example (excluding Examples 6, 7, and Comparative Examples 1-3) are placed on the rough surface of the copper foil, and heated and pressed using a mold frame hot press at a pressure of 5 MPa, 120°C for 30 minutes, then 150°C for 30 minutes, and then 180°C for 120 minutes, to obtain a laminated body in which the sheet and the copper foil are bonded and cured.

[0240] The copper foil was stacked on the Teflon sheet on the glass plate with the rough surface facing upward, and a Teflon (registered trademark) mold frame (thickness 0.3 mm) was set on it. The composition obtained in Examples 6, 7, and Comparative Examples 1 to 3 was poured into it, and the Teflon sheet and the glass plate were further stacked, and a load was applied to make them close, and they were heated at 120°C for 30 minutes, 150°C for 30 minutes, and then 180°C for 120 minutes to cure. After curing, the glass plate, Teflon (registered trademark) sheet and mold frame were removed to obtain a laminated body in which the sheet and the copper foil were bonded and cured.

[0241] <Brittleness temperature (low temperature brittleness)>

[0242] The measurement was performed in accordance with JIS K 7216:1980. The compositions obtained in Examples 1 to 10 and Comparative Examples 1 to 4 were molded into test pieces B for embrittlement testing, and the samples obtained by curing them under the same conditions as the pieces all had embrittlement temperatures of less than -10°C. The low-temperature brittleness in Table 2 is indicated by ○ (good). On the other hand, the brittle temperatures of the samples obtained in Comparative Examples 3 and 4 were higher than -5°C. The low-temperature brittleness in Table 2 is indicated by × (poor).

[0243] <Olefin-aromatic vinyl compound-aromatic polyene copolymer>

[0244] The copolymer P-8 was obtained by referring to the production methods of Japanese Patent Application Laid-Open Nos. 2009-161743 and 2010-280771 and appropriately changing the monomer amount, ratio, polymerization pressure and polymerization temperature.

[0245] The total of the olefin monomer unit (ethylene), the aromatic vinyl compound monomer unit (styrene), and the aromatic polyene monomer unit (divinylbenzene) is set to 100% by mass. Table 3 shows the composition, number average molecular weight, and glass transition temperature of the copolymer.

[0246] [Table 3]

[0247]

[0248] Embodiment 11

[0249] P-8 was used to prepare a varnish using toluene as a solvent in the proportions (parts by mass) shown in Table 4, and a soft resin-like uncured sheet and a cured sheet thereof were prepared in the same manner as in Examples 8 to 10. As a polar monomer, bismaleimide BMI-3000H (meta-phenylene bismaleimide) manufactured by Yamato Chemical Industry Co., Ltd. was used. Evaluation was performed in the same manner as above, and the measured values ​​are shown in Table 4.

[0250] Example 12

[0251] P-8 was used to prepare a varnish using toluene as a solvent in the proportion (mass parts) shown in Table 4, and a soft resin-like uncured sheet and a cured sheet thereof were prepared in the same manner as in Examples 8 to 10. As a raw material, a fused silica filler SFP-130MC manufactured by Denka Co., Ltd. was used. 40% by volume of the silica filler was used relative to 60% by volume of the resin component. Evaluation was performed in the same manner as above, and the measured values ​​are shown in Table 4.

[0252] [Table 4]

[0253]

[0254] The ratios in the table are expressed in parts by mass. ☆40 vol% relative to 60 vol% of the resin component

[0255] Embodiment 13, 14

[0256] <Evaluation as an adhesive between copper foil and LCP (liquid crystal polymer) sheet>

[0257] Using the varnish obtained in Example 11 and the varnish obtained in Example 12 (wherein the varnish before adding silica filler), the adhesion between copper foil and LCP sheet was evaluated in the following manner. As copper foil, the above copper foil was used, and as LCP sheet, LCP resin (model A-5000, melting point 280°C) manufactured by Ueno Pharmaceutical Co., Ltd. and a sheet with a thickness of 100 μm obtained by the method described in International Publication No. WO2020 / 153391 were used. The varnish was applied to the LCP sheet, the solvent was first removed by air drying at 60°C, and then the solvent was carefully and fully removed at 60°C, normal pressure to vacuum in a non-foaming manner. The thickness of the varnish layer after removing the solvent is about 50 μm. The rough surface of the copper foil is made to fit the varnish side of the sheet from which the solvent has been removed, and the press is applied at 5 MPa with a press under vacuum, while heating and curing at 120°C for 30 minutes, 150°C for 30 minutes, and then 180°C for 120 minutes. The sheet was cut into pieces with a width of 10 mm and a length of 100 mm, and the peel strength between the LCP sheet and the copper foil was measured and evaluated at 90° peeling according to Japanese Industrial Standard (JIS) C6481:1996. When the varnish obtained in Example 11 was used, the peel strength was 1.7 N / mm. When the varnish obtained in Example 12 (which did not contain silica filler) was used, it was 1.3 N / mm. The peeling surface was observed, and it was found that peeling occurred at the interface between the cured product derived from the varnish and the LCP sheet. Therefore, it was concluded that the peel strengths of the LCP sheet and the cured product derived from the varnish were 1.7 N / mm and 1.3 N / mm, respectively. In addition, in the same test piece, the peel strengths of the copper foil and the cured product derived from the varnish were found to be higher than the above values.

[0258] Comparative Example 5

[0259] Only the copper foil and the LCP sheet were used and heat-pressed by a press machine under the same conditions as in Examples 11 and 12, but the two were not substantially bonded.

[0260] According to the above results, the cured product formed by curing the composition of the present invention has an excellent high elastic modulus under high temperature conditions, presents a specific range of elastic modulus, good breaking strength, elongation at break, presents low water absorption, low dielectric properties (low dielectric constant, loss tangent). In addition, the peel strength with copper foil is also sufficient strength in actual use. In addition, a low brittle temperature is presented, and cold resistance is also high. In addition, LCP (liquid crystal polymer) sheets can also present high peel strength under relatively mild conditions. Therefore, it can be preferably used as an electrical insulating material for high frequency. With regard to the present invention, in particular, the composition of the present invention can be used as a protective layer film, a solder mask, a laminated film, a bonding sheet, a protective layer sheet, a bump sheet for a flip chip bonding machine, an interlayer insulating agent, and an interlayer adhesive in an uncured state. They can be cured and used by laminating, coating, impregnation, etc. with other components. After curing, the composition of the present invention can be used as a printed substrate, a flexible printed substrate, and a FCCL (flexible copper-clad laminate) substrate. In addition, it can be used as an insulating layer for CCL substrates and PCB substrates.

Claims

1. A method for producing an uncured or semi-cured molded body, characterized in that: The manufacturing method comprises the following steps: A step of preparing a varnish-like composition comprising an olefin-aromatic vinyl compound-aromatic polyene copolymer satisfying the following conditions (1) to (4) and a solvent, (1) the number average molecular weight of the copolymer is 5000 or more and 100,000 or less, (2) the aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 10% by mass or more and less than 60% by mass, (3) the aromatic polyene is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylidene groups in the molecule, and the vinyl content derived from the aromatic polyene unit is 3 to less than 20 in terms of number average molecular weight, (4) the olefin is one or more selected from olefins having 2 to 20 carbon atoms, the olefin is ethylene alone, or the mass ratio of the α-olefin monomer component other than ethylene contained in the olefin to the ethylene monomer component is 1 / 10 or less, and the total of the olefin monomer unit, the aromatic vinyl compound monomer unit and the aromatic polyene monomer unit is 100 mass %; The step of applying the varnish-like composition to a substrate or impregnating the substrate with the composition; and The step of removing the solvent from the substrate.

2. The manufacturing method according to claim 1, wherein: The composition further comprises at least one selected from the group consisting of an added resin, a curing agent, a polar monomer, a filler, a flame retardant, and a surface modifier.

3. The manufacturing method according to claim 1 or 2, wherein: The composition does not include non-polar monomers.

4. The manufacturing method according to claim 1 or 2, wherein: The composition contains 1 to 500 parts by mass of one or more additional resins selected from the group consisting of hydrocarbon elastomers, polyphenylene ether resins, and aromatic polyene resins, relative to 100 parts by mass of the copolymer.

5. The manufacturing method according to claim 1 or 2, wherein: In the composition, the vinyl content of the aromatic polyene unit is 3.5 or more and less than 20 in terms of number average molecular weight.

6. An uncured or semi-cured molded body obtained by the production method according to any one of claims 1 to 5.

7. A cured product, which is a cured product of the uncured or semi-cured molded product according to claim 6.

8. The cured product according to claim 7, wherein the dielectric constant at 10 GHz is 3.0 or less and 2.0 or more, the loss tangent is 0.005 or less and 0.0003 or more, and the storage modulus at 300°C is 5×10 5 Pa or more, and the tensile modulus of elasticity measured at 23° C. is less than 3 GPa and 5 MPa or more.

9. A method for producing a laminate, comprising the following steps: The step of laminating the uncured or semi-cured molded body according to claim 6 and the metal foil, and The step of heating and pressurizing the laminated molded body and metal foil. 10 . A laminate obtained by the production method according to claim 9 .

11. The laminate according to claim 10, wherein The peel strength between the composition and the metal foil is 1.0 N / mm or more when measured in accordance with Japanese Industrial Standard (JIS) C6481:1996.

12. A method for producing a laminate, comprising the following steps: A step of preparing a varnish-like composition comprising an olefin-aromatic vinyl compound-aromatic polyene copolymer satisfying the following conditions (1) to (4) and a solvent, (1) the number average molecular weight of the copolymer is 5000 or more and 100,000 or less, (2) the aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 10% by mass or more and less than 60% by mass, (3) the aromatic polyene is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylidene groups in the molecule, and the vinyl content derived from the aromatic polyene unit is 3 to less than 20 in terms of number average molecular weight, (4) the olefin is one or more selected from olefins having 2 to 20 carbon atoms, the olefin is ethylene alone, or the mass ratio of the α-olefin monomer component other than ethylene contained in the olefin to the ethylene monomer component is 1 / 10 or less, and the total of the olefin monomer unit, the aromatic vinyl compound monomer unit and the aromatic polyene monomer unit is 100 mass %; The step of applying the composition in a varnish form to a metal foil; and The composition is cured by removing the solvent from the applied composition, so that the dielectric constant of the cured product is 3.0 or less and 2.0 or more at 10 GHz, the loss tangent is 0.005 or less and 0.0003 or more, and the storage modulus at 300° C. is 5×10 5 Pa or more, and the tensile elastic modulus measured at 23° C. is less than 3 GPa and 5 MPa or more.

13. The manufacturing method according to claim 12, wherein: The composition further comprises at least one selected from the group consisting of an added resin, a curing agent, a polar monomer, a filler, a flame retardant, and a surface modifier.

14. The manufacturing method according to claim 12 or 13, wherein: The composition does not include non-polar monomers.

15. The manufacturing method according to claim 12 or 13, wherein: In the composition, the vinyl content of the aromatic polyene unit is 3.5 or more and less than 20 in terms of number average molecular weight. 16 . A laminate obtained by the production method according to claim 12 .

17. The laminate according to claim 16, wherein The peel strength between the composition and the metal foil is 1.0 N / mm or more when measured in accordance with Japanese Industrial Standard (JIS) C6481:1996.

18. A varnish-like composition comprising an olefin-aromatic vinyl compound-aromatic polyene copolymer satisfying the following conditions (1) to (4) and a solvent, (1) The number average molecular weight of the copolymer is 5000 or more and 100,000 or less; (2) the aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 10% by mass or more and less than 60% by mass; (3) the aromatic polyene is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl and / or vinylidene groups in the molecule, and the vinyl content derived from the aromatic polyene unit is 3.5 to less than 20 in terms of number average molecular weight; (4) The olefin is one or more olefins having a carbon number of 2 or more and 20 or less, the olefin is ethylene alone, or the mass ratio of the α-olefin monomer component other than ethylene contained in the olefin to the ethylene monomer component is 1 / 10 or less, and the total of the olefin monomer unit, the aromatic vinyl compound monomer unit and the aromatic polyene monomer unit is 100 mass %.

19. The composition according to claim 18, further comprising at least one selected from the group consisting of an additional resin, a curing agent, a polar monomer, a filler, a flame retardant, and a surface modifier.

20. The composition of claim 18 or 19, which does not contain non-polar monomers.

21. The composition according to claim 18 or 19, comprising 1 to 500 parts by mass of one or more additional resins selected from the group consisting of hydrocarbon elastomers, polyphenylene ether resins and aromatic polyene resins, relative to 100 parts by mass of the copolymer.